Strategi Marketing Digital Homestay Dalam Upaya Pengembangan Desa Wisata Tambong Kabupaten Banyuwangi - Bitsyi Naviri Ismaniar; Beby Dwi Febriyanti; Khoirunisa, Khoirunisa; Dheanita Sekarini Octanisa; Reni Nur Jannah (CV. ITTC INDONESIA, 2025)
This community service aims to enhance the digital marketing skills of homestay operators in Tambong Village to support the development of the tourism village. Through training and mentoring, participants were introduced to the use of social media, OTA (Online Travel Agent) platforms, and Google My Business. The activity involved local tourism awareness groups (Pokdarwis), village-owned enterprises (BUMDes), and village officials. The results showed improved digital literacy, increased homestay visibility, and enhanced competitiveness of the destination on online platforms. This strategy proved effective in expanding market reach, encouraging community participation, and strengthening the local economy through sustainable tourism. Digital transformation is a crucial step toward building an independent and competitive tourism village.